PENGARUH CARIOCA EXERCISE TERHADAP PENINGKATAN KELINCAHAN ANAK LAKI-LAKI USIA 8-10 TAHUN - Febriani, Yelva; Sy, Resti Hilmy (Universitas Fort De Kock, 2025)
Agility is an individual's ability to change positions in certain areas. Individuals who can move to different positions at great speed and maximize good body coordination have good personal agility. This study aims to see the effect of Carioca exercise in increasing agility in boys aged 8-10 years. This type of research is quantitative using a quasi-experimental research design with one group pre and posttest design. The sample collection technique used a purposive sampling method with a total of 10 samples that met the inclusion criteria. The intervention was given 12 times with 1 rest day for 4 weeks with training 3 times a week. Increased agility was measured using the Illinois Agility Run Test. The results of univariate analysis showed that the average agility before carioca exercise intervention was 22.22 and the average agility after being given carioca exercise was 19.71. Bivariate results show that there is a difference in average agility with a P value = 0.000<a (0.05). Therefore, it is recommended that schools integrate the carioca exercise intervention method into sports learning at school to increase student agility.